Sobre la futura Historia de la lengua de Menéndez Pidal - Francisco Abad Nebot (Estudios de Lingüística, 2003)
This article presents the published parts of the future Ramón Menéndez Pidal's Historia de la lengua española, and also makes reference to another Menéndez Pidal works related with the former book. Likewise, we will talk about some theoretical notions on D. Ramón's linguistics as well as about his mentality thoroughly linked to krausism.